EXPLORING MEANINGFUL CHILD PARTICIPATION IN GOVERNANCE: INSIGHTS FROM BARANGAY LOCAL GOVERNMENT UNITS IN SOUTHERN PHILIPPINES - Argie Khim Ormilla; Christine Tenorio (Indonesian Journal of Social Sciences, Policy and Politics, 2024)
This study examines how the selected barangay local government units (BLGUs) in the Southern Philippines are implementing meaningful child participation in governance. It focuses on three key aspects: informing children of their rights, actively hearing their perspectives, and involving them in decision-making. The study found a diverse group of respondents, with a majority from Gen Z and Millennials. Many are college graduates and actively involved in organizations, showcasing their potential as future leaders. A significant effort is put into ensuring children are well-informed about their rights under the UN Convention on the Rights of the Child (UNCRC). This highlights a commitment to both inclusivity and upholding children's rights. The research also found a positive perception towards "hearing" children's voices. This suggests a cultural shift towards participatory governance, where children's perspectives are valued in decision-making. This empowers them, communicates the importance of their opinions, and leads to policies that better reflect their needs. The study concludes that meaningful child participation is not only achievable but essential for sustainable development and good governance. It's an investment in the future, fostering a generation of informed, engaged, and responsible citizens. These findings offer valuable insights for local governments in Southern Philippines and contribute to the global discussion on empowering children as active contributors to society. Secure spaces for participation and formal structures within schools, communities, or local government, like the Sangguniang Kabataan (SK), can further empower children to effectively engage in governance.